2017
DOI: 10.2214/ajr.16.17711
|View full text |Cite
|
Sign up to set email alerts
|

Hypervascular Transformation of Hypovascular Hypointense Nodules in the Hepatobiliary Phase of Gadoxetic Acid–Enhanced MRI: A Systematic Review and Meta-Analysis

Abstract: Hypovascular hypointense nodules detected in the hepatobiliary phase of gadoxetic acid-enhanced MRI carry a significant potential of transforming into hypervascular HCCs. The size of nodules is a significant risk factor for hypervascular transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…As an inherent strength of HBA‐MRI, one subcentimeter‐sized HCC (9 mm) and two DNs (7 and 16 mm) were depicted only on HBP images but were not clearly seen on other sequences or ECA‐MRI. There is little evidence regarding the clinical impact of early detection and early treatment for such early HCCs and risky nodules progressing to overt hypervascular HCC in terms of patient outcomes . Given that such risky nodules might not be a “target lesion” for treatment but a “signaling lesion” for second overt hypervascular HCC, early recognition of such nodules will usually lead a clinician to follow up with caution .…”
Section: Discussionmentioning
confidence: 99%
“…As an inherent strength of HBA‐MRI, one subcentimeter‐sized HCC (9 mm) and two DNs (7 and 16 mm) were depicted only on HBP images but were not clearly seen on other sequences or ECA‐MRI. There is little evidence regarding the clinical impact of early detection and early treatment for such early HCCs and risky nodules progressing to overt hypervascular HCC in terms of patient outcomes . Given that such risky nodules might not be a “target lesion” for treatment but a “signaling lesion” for second overt hypervascular HCC, early recognition of such nodules will usually lead a clinician to follow up with caution .…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] A recent meta-analysis of such nodules reported a pooled rate of hypervascular transformation of 28% (95% CI, 23-34%) overall, with the pooled 1-, 2-, and 3-year cumulative incidence rates of 18% (95% CI, 9-27%), 25% (95% CI, 12-38%), and 30% (95% CI, 19-42%), respectively. 41 Conversely, only 1-4% of HBP hyperintense nodules without APHE progress to HCC, with a 1-year hypervascularization rate of 0.4-2%. 42,43 In addition to increased risk of progression to HCC, HBP hypointense nodules without APHE are markers of increased HCC development elsewhere in the liver: the cumulative 3-year rate of HCC at sites different from the original HBP hypointense nodules without APHE is reported to be 22%, compared with 6% in patients with no nodules.…”
Section: Potential Advantages Of Gadoxetatementioning
confidence: 99%
“…Of newly developed arterially hyperenhancing HCCs, 29–44% were visible as HBP hypointense nodules without APHE on prior imaging . A recent meta‐analysis of such nodules reported a pooled rate of hypervascular transformation of 28% (95% CI, 23–34%) overall, with the pooled 1‐, 2‐, and 3‐year cumulative incidence rates of 18% (95% CI, 9–27%), 25% (95% CI, 12–38%), and 30% (95% CI, 19–42%), respectively . Conversely, only 1–4% of HBP hyperintense nodules without APHE progress to HCC, with a 1‐year hypervascularization rate of 0.4–2% .…”
Section: Potential Advantages Of Gadoxetatementioning
confidence: 99%
“…3436 According to Suh et al, 37 a hypointense nodule in the hepatobiliary phase of gadoxetate-enhanced MRI that is nonhypervascular in the arterial phase should be regarded as intermediate risk, whereas one that is hypervascular in the arterial phase should be considered high risk (Fig. 12).…”
Section: Contrast Agents Available For Use In Mri For Diagnosis Of Hccmentioning
confidence: 99%
“…26,34 Several studies have shown that MRI performed with hepatobiliary contrast agents provides higher sensitivity compared to dynamic contrast-enhanced CT for the detection of HCC, as well as liver metastases. [34][35][36] According to Suh et al, 37 a hypointense nodule in the hepatobiliary phase of gadoxetate-enhanced MRI that is nonhypervascular in the arterial phase should be regarded as intermediate risk, whereas one that is hypervascular in the arterial phase should be considered high risk (Fig. 12).…”
Section: Contrast Agents Available For Use In Mri For Diagnosis Of Hccmentioning
confidence: 99%